2014
DOI: 10.5664/jcsm.3700
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia is a Key Correlate of EEG Activation and Daytime Sleepiness in Hypercapnic Sleep Disordered Breathing Patients

Abstract: Background:The key determinants of daytime drowsiness in sleep disordered breathing (SDB) are unclear. Hypercapnia has not been examined as a potential contributor due to the lack of reliable measurement during sleep. To overcome this limitation, we studied predominantly hypercapnic SDB patients to investigate the role of hypercapnia on EEG activation and daytime sleepiness. Methods: We measured overnight polysomnography (PSG), arterial blood gases, and Epworth Sleepiness Scale in 55 severe SDB patients with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…We recently observed that hypercapnic SDB patients (n=97) had paradoxically high percentage of slow wave sleep; awake pCO 2 measured by ABG was the best predictor for the slowing of EEG [12]. There was a crosscorrelation between a reduced wake paCO 2 , a faster sleep EEG (reduced Delta/Alpha ratio) and reduced daytime sleepiness during positive airway pressure treatment in hypercapnic SDB patients [11]. Multiple regression analyses showed that the degree of change in hypercapnia but not hypoxia was the only significant predictor of both the Delta/Alpha ratio and daytime sleepiness [11].…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…We recently observed that hypercapnic SDB patients (n=97) had paradoxically high percentage of slow wave sleep; awake pCO 2 measured by ABG was the best predictor for the slowing of EEG [12]. There was a crosscorrelation between a reduced wake paCO 2 , a faster sleep EEG (reduced Delta/Alpha ratio) and reduced daytime sleepiness during positive airway pressure treatment in hypercapnic SDB patients [11]. Multiple regression analyses showed that the degree of change in hypercapnia but not hypoxia was the only significant predictor of both the Delta/Alpha ratio and daytime sleepiness [11].…”
mentioning
confidence: 93%
“…There was a crosscorrelation between a reduced wake paCO 2 , a faster sleep EEG (reduced Delta/Alpha ratio) and reduced daytime sleepiness during positive airway pressure treatment in hypercapnic SDB patients [11]. Multiple regression analyses showed that the degree of change in hypercapnia but not hypoxia was the only significant predictor of both the Delta/Alpha ratio and daytime sleepiness [11]. In healthy subjects, there is also a positive linear relationship between the increasing hypercapnia and the slowing of EEG (increased Delta/Alpha ratio), while hypoxia did not show such an effect [13].…”
mentioning
confidence: 93%
See 3 more Smart Citations